Peran Academic Self-Efficacy dalam memediasi Pengaruh Job Demands dan Time Management terhadap Academic Performance pada Mahasiswa yang Bekerja - Risma Callista Athallah; Osly Usman (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The phenomenon of university students simultaneously undertaking academic studies and employment has become increasingly common, creating unique challenges in balancing work responsibilities and academic obligations. This study aims to examine the effects of job demands and time management on academic performance, with academic self-efficacy serving as a mediating variable among undergraduate and postgraduate students who work while pursuing higher education. The research employed a quantitative approach using a causal research design. Data were collected through an online questionnaire administered to 50 working students selected through purposive sampling. The study measured four variables, namely job demands, time management, academic self-efficacy, and academic performance. Data were analyzed using multiple regression analysis, Baron and Kenny’s causal steps approach, and the Sobel test to examine mediation effects. The findings reveal that time management has a positive and significant effect on both academic self-efficacy and academic performance. Academic self-efficacy also demonstrates a positive and significant influence on academic performance and emerges as the strongest predictor in the model. In contrast, job demands do not significantly affect either academic self-efficacy or academic performance. Furthermore, academic self-efficacy does not mediate the relationship between job demands and academic performance. However, academic self-efficacy fully mediates the relationship between time management and academic performance, indicating that effective time management enhances students’ confidence in their academic abilities, which subsequently improves their academic outcomes. These findings highlight the importance of strengthening time management skills and academic self-efficacy to support the academic success of working students in higher education institutions.